The strengths of second language learning (Global Journal of Human-Social Science, 2025)
The world has become an arena in which things change rapidly It does no take longer centuries nor decades for cutting edge values and tools to find themselves outdated Research has moved to an unprecedented level of light speed changes Stemming from this premise this review explores current practices in second language learning It delves into various assets associated with second language learning nowadays Surprisingly the practice despite the challenges there pertaining displays numerous advantages worth pointing out in an ever evolving and fast changing world